Responsabilidade dos sócios na sociedade limitada - Mashimo, Claucio (2008)
The issue of partners liability in limited liability companies is object of extensive considerations of the part of entrepreneurs, in view of the likelihood of being made liable and having their properties, gathered throughout their lives, seized, due to exceptions to the rule provided for in article 1,052, Civil Code. Pursuant thereto, the partners are jointly liable for paying the capital stock, and, once it has taken place, the liability shall be limited to the share of each one. This paper will examine the main aspects of such liability, its exceptions, the cases that may arise from this legal provision and those arising from the mere jurisprudential construction. As for the Disregard Doctrine, we will review the application of existing theories to concrete cases. Finally, we will make a comparison review between Partners Liability in Limited Liability Companies and the Theory of Disregard of Legal Entity, by attempting to show the difference between such two institutions